PENGARUH MODAL INTELEKTUAL PADA KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Eva Dwi Rukmana, 10.05.52.0134; Suwarti, Titiek (Students Journal of Accounting and Banking, 2014)
This study aims to examine the influence of Value Added Intellectual (VIC), Market to Book Value (MBV), Intellectual Capital Disclosure (ICD), and Good Corporate Governance (ICG) on the financial performance of companies in the banking companies listed in Indonesia Stock Exchange (IDX). This study used purposive sampling with a sample of 27 companies. Secondary data was obtained through IDX (Indonesian Stock Exchange), Annual Report, and the company ICMD banking companies listed in Indonesia Stock Exchange (IDX) 2010-2012. Method of analysis used is multiple linear regression analysis to explain the relationship between these variables. These results indicate that all variables simultaneously Value Added Intellectual (VAIC), Market to Book Value (MBV), Intellectual Capital Disclosure (ICD), and Good Corporate Governance (ICG) on the financial performance of the company. Whreas in partial,variable Market to Book Value (MBV) a significant positive effect, variable Value Added Intellectual (VAIC), Intellectual Capital Disclosure (ICD), and Good Corporate Governance (ICG) significant negative effect on the financial performance of the company. Keywords: VAIC, MBV, ICD, GCG, ROA